Sewaka Suntingan Teks dan Terjemahan - , M. PANDU W ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Sewaka is a valuable resoursce taken from the transcribed manuscript Kempalan Serat Piwulang (Library code 0032/PP/73 Pi 8). The Sewaka manuscript is written in Dandanggula, a form of Javanese poetry, which contains many meaningful lessons The lessons within Sewaka illustrate life lessons, particularly in regard to hard work. The manuscript details ways in which to work positively, what one must avoid in their work and why. This paper outlines the research done on the Sewaka manuscript and its presentation of transliteration and translation. The transliteration was diplomatically presented in order to maintain authenticity and well editted for reader comprehension. Due this, the result is a manuscript which was successfully translated literally and freely from Javanese into Indonesian